Single-cell RNA sequencing uncovers cellular heterogeneity and the progression of heterotopic ossification of the elbow - Zhang, Chi; Xiao, Dan; Shu, Li; Gong, Maoqi; Liu, Xinghua; Jiang, Xieyuan (Frontiers in Pharmacology, 2024)
Heterotopic ossification of the elbow (HOE) is a complicated pathologic process characterized by extra bone formation in the elbow. Bone formation is a complex developmental process involving the differentiation of mesenchymal stem cells into osteoblasts. The aim of this study was to explore the cellular origin and progression of HOE by single-cell RNA sequencing. We identified 13 clusters of cells in HOE and further analyzed the subclusters for 4 of the main cell types. Six subclusters of osteoblasts, nine subclusters of chondrocytes, six subclusters of fibroblasts, and five subclusters of mononuclear phagocytes (MPs) were identified and analyzed. The new findings on osterix (OSX) and SOX9 expression in osteoblast subclusters and chondrocyte subclusters indicate that HOE is mediated through endochondral ossification. Further identification of the corresponding signature gene sets of distinct subclusters indicated that subclusters of osteoblasts_3, osteoblasts_4, osteoblasts_5, and osteoblasts_6 are relatively more mature during the osteoblastic progression of HOE. The trajectory analysis of the osteoblasts demonstrated that some genes were gradually downregulated, such as CRYAB, CCL3, SFRP4, WIF1, and IGFBP3, while other critical genes were upregulated, such as VCAN, IGFBP4, FSTL1, POSTN, MDK, THBS2, and ALPL, suggesting that these factors may participate in HOE progression. Cell–cell communication networks revealed extensive molecular interactions among the 13 HOE clusters. Ligand–receptor pairs for IL6, COL24A1, COL22A1, VWF, FZD6, FGF2, and NOTCH1 were identified, suggesting that multiple signaling pathways may be involved in HOE. In conclusion, this study provided the cellular atlas for HOE. We have established a greater extent of the heterogeneity of HOE cells than previously known through transcriptomic analysis at the single-cell level. We have observed gradual patterns of signature gene expression during the differentiation and maturation progression of osteoblasts from stem cells in HOE with higher resolution. The cell heterogeneity of HOE deserves further investigation to pave the way for identification of potential targets for HOE early diagnosis and therapeutic treatment.